Joyful Learning with Gamification: Development of Indonesian Language Learning Media in MI - Fithriyah, Dewi Niswatul; Suttrisno, Suttrisno; Sa'diyah, Zumrotus; Agustina, Saskia; Krisnanda, Made (Journal of Elementary Educational Research, 2025)
Education in the 4.0 era demands learning media that are enjoyable, interactive, and capable of increasing student motivation at the elementary school level. Preliminary findings at MI Nurul Huda Temayang revealed that Indonesian language learning, particularly capitalization material, is still monotonous and teacher-centered, resulting in low student engagement. This study aims to develop a gamification-based learning media integrating Google Sites, Canva, and Wordwall to enhance students’ motivation, engagement, and comprehension. This study employed a Research and Development (R&D) method using the ADDIE model involving 30 third-grade students. Data were collected through observation, interviews, motivation questionnaires, and learning outcome tests. The results showed that students became more active, motivated, and demonstrated better conceptual understanding. The developed gamification-based learning media proved to be feasible and effective in creating enjoyable and meaningful Indonesian language learning in elementary schools.